Process for the preparation of a multi-metal oxide containing a hindered lewis acid-base pair and its use

CN118892842BActive Publication Date: 2026-11-03JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410928797.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2026-11-03
Estimated Expiration
2044-07-11

AI Technical Summary

Technical Problem

In existing oxidative desulfurization technologies, oxygen molecules are difficult to activate sulfides, and there are few reports on heterogeneous catalysts based on iron oxide in the field of oxidative desulfurization. Modification is required to improve catalytic performance.

Method used

Transition metals are introduced into metal oxide lattices through atomic doping strategies to form hindered Lewis acid-base pairs. The metal sites adjacent to the doped atoms serve as Lewis acid sites, and the doped atoms adjacent to the oxygen vacancies serve as Lewis base sites, thus constructing a synergistic catalytic environment.

Benefits of technology

It achieves efficient adsorption and activation of oxygen and sulfur-containing compounds. The catalyst exhibits excellent oxidative desulfurization performance, with high activity and easy separation characteristics, and no by-products are generated, thus achieving deep desulfurization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118892842B_ABST
    Figure CN118892842B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of material preparation, and discloses a preparation method of a multi-metal oxide containing a hindered Lewis acid-base pair and application thereof. The multi-metal oxide is prepared by first encapsulating a transition metal source in a metal organic framework and then realizing the preparation of a doped multi-metal oxide through a high-temperature calcination method. The catalyst is rich in a hindered Lewis acid-base pair, wherein metal atoms adjacent to a doping atom serve as Lewis acid sites, and rich-electron oxygen vacancies in the structure serve as Lewis base sites. The catalyst prepared by the application is non-toxic and harmless, has high catalytic activity, is easy to recycle, and has high desulfurization performance on various aromatic sulfur-containing organic matters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional material preparation technology, and in particular relates to a multi-metal oxide catalyst containing hindered Lewis acid-base pairs, and further provides a method for preparing the catalyst and its application in catalytic oxidation desulfurization of diesel. Background Technology

[0002] Currently, hydrodesulfurization (HDS) is the most widely used desulfurization technology in industry. However, because thiophene sulfides in fuel oil have a more complex structure than aliphatic sulfides, their removal requires stringent conditions, leading to increased production costs for enterprises. Therefore, it is necessary to find new desulfurization technologies to assist in achieving deep desulfurization of fuel oil. Oxidative desulfurization technology is considered one of the promising desulfurization methods due to its mild reaction conditions and low energy consumption.

[0003] In oxidative desulfurization using oxygen as the oxidant, the oxygen molecule, being in its inert triplet ground state, is difficult to activate sulfides. Therefore, a highly efficient catalyst is needed to co-activate molecular oxygen and sulfur-containing substrates. Transition metal oxides exhibit high activity in the cleavage and transformation of CS bonds in aromatic sulfur-containing compounds and are therefore frequently used in oxidative desulfurization. However, heterogeneous catalysts based on iron oxide, while possessing a stable electronic structure, are rarely reported in the field of oxidative desulfurization. Therefore, to further improve the application of metal-based catalysts in oxidative desulfurization, modification is necessary.

[0004] Atomic doping is one of the most effective methods for adjusting the electronic structure of catalysts. By altering the surface acidity or basicity of the metal through the synergistic effect between the host and doped metal atoms, weakly basic aromatic sulfur-containing compounds can be effectively adsorbed. Furthermore, the research revealed that hindered Lewis acid-base pairs (FLPs) are a class of Lewis acid-base pairs with special reactivity, allowing Lewis acids and bases to exist independently as electron acceptors and donors, thereby activating small molecules.

[0005] However, current research has not reported on the activation of molecular oxygen desulfurization by host multimetal catalysts containing hindered Lewis acid-base pairs. Therefore, it is necessary to report a new technical solution. Summary of the Invention

[0006] To address the problems existing in current research and technology, the present invention aims to provide a multi-metal oxide catalyst containing hindered Lewis acid-base pairs for catalytic desulfurization of diesel fuel. This invention employs an atomic doping strategy to dope transition metal atoms into the metal oxide lattice, where the metal sites adjacent to the doped atoms serve as Lewis acid sites, and the doped atoms adjacent to oxygen vacancies serve as Lewis base sites, thus obtaining a multi-metal oxide catalyst containing hindered Lewis acid-base pairs. The independent Lewis acid sites in the hindered Lewis acid-base pair structure adsorb and activate aromatic organic sulfur compounds, while the independent Lewis base sites effectively activate molecular oxygen, forming a synergistic catalytic environment and improving the performance of oxidative desulfurization.

[0007] Another technical problem to be solved by the present invention is to provide a preparation process for the above-mentioned multi-metal oxide catalyst containing hindered Lewis acid-base pairs.

[0008] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a polymetallic oxide containing hindered Lewis acid-base pairs includes the following steps: (1) Dissolve the transition metal dopant source and the coordination metal source in a mixed solution of N,N-dimethylformamide and ethylene glycol. After stirring until there are no obvious particles, add a certain amount of 1,3,5-benzenetricarboxylic acid and stir thoroughly to form a homogeneous mixture. (2) The mixture prepared in step (1) is added to the polytetrafluoroethylene liner and subjected to a solvothermal reaction at a certain temperature. After the reaction is completed, it is cooled to room temperature, centrifuged, washed with anhydrous ethanol, and dried to obtain the catalyst precursor. (3) The precursor sample obtained in step (2) is placed in a tube furnace and heated to the calcination temperature in a gas atmosphere at a certain heating rate to obtain a multi-metal oxide catalyst containing hindered Lewis acid-base pairs.

[0009] In step (1), the transition metal doping source is one or more of ammonium molybdate tetrahydrate, ammonium molybdate, ammonium tungstate, ammonium metavanadate or titanate, preferably ammonium molybdate tetrahydrate.

[0010] The coordination metal source is one of ferric chloride hexahydrate, ferric nitrate nonahydrate, chromium nitrate, aluminum nitrate nonahydrate, and vanadium trichloride; preferably ferric chloride hexahydrate.

[0011] In the transition metal doped source and the coordination metal source, the molar ratio of metal ions is 0.5:10 to 3:10; In a mixed solution of N,N-dimethylformamide and ethylene glycol, the volume ratio of N,N-dimethylformamide to ethylene glycol is 1:1. The molar ratio of 1,3,5-benzenetricarboxylic acid to the coordinating metal source is 1.5~2:1.

[0012] In step (2), the temperature of the solvothermal reaction is 100~140℃ and the time is 6-18 hours.

[0013] In step (3), the heating rate is 5~10℃ / min, the calcination temperature is 400~800℃, and the calcination time is 1~6h. The gas atmosphere is: air, oxygen, or a mixed gas containing a certain oxygen component.

[0014] The present invention provides a multi-metal oxide catalyst containing hindered Lewis acid-base pairs. It is a powdery solid and is immiscible with water, ethanol, acetonitrile, gasoline, diesel, and other liquids, making it an environmentally friendly catalyst.

[0015] Furthermore, the polymetallic oxide containing hindered Lewis acid-base pairs prepared by this invention can be applied to the removal of aromatic sulfur-containing compounds from diesel fuel through catalytic oxidation. The specific steps are as follows: The polymetallic oxide containing hindered Lewis acid-base pairs prepared according to this invention was added to simulated diesel fuel containing aromatic sulfides. Oxygen was introduced, and the mixture was stirred in a constant-temperature oil bath at a temperature of 110–130°C and a stirring speed of 600 rpm. The upper oil phase was taken for sulfur content testing. After the reaction was complete, the oil phase and catalyst phase were centrifuged, washed, and dried for recycling.

[0016] The simulated diesel fuel containing aromatic sulfides is prepared by dissolving dibenzothiophene (DBT), 4-methyldibenzothiophene (4-MDBT), and 4,6-dimethyldibenzothiophene (4,6-DMDBT) in dodecane, with a sulfur content of 200 mg / kg. -1 .

[0017] In the above desulfurization steps, the ratio of polymetallic oxides containing hindered Lewis acid-base pairs to simulated diesel oil is 5~20mg:20mL; The oxidant is oxygen, and the flow rate is 80–120 mL / min.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The invention utilizes an atomic doping strategy to dope transition metals such as molybdenum, tungsten, vanadium, and titanium into the lattices of iron oxide, zirconium oxide, vanadium oxide, and aluminum oxide, thereby adjusting the electronic structure of the catalyst. This results in abundant Lewis acid sites in the metal oxide structure, with doped atoms near oxygen vacancies serving as Lewis base sites. Due to steric hindrance, hindered Lewis acid-base pairs are formed. The independently existing Lewis acid-base pairs in this catalyst can achieve adsorption and activation of oxygen molecules and sulfur-containing substrate molecules, thus exhibiting excellent catalytic performance in diesel oxidative desulfurization. However, previous research reports have not included the application of hindered Lewis acid-base pairs in oxidative desulfurization.

[0019] (2) The multi-metal oxide catalyst containing hindered Lewis acid-base pairs of the present invention has the characteristics of high activity and easy separation of heterogeneous catalysts, and its activity has good cycle stability, which can achieve deep desulfurization. At the same time, no other by-products are generated during the desulfurization process.

[0020] (3) The multi-metal oxide catalyst containing hindered Lewis acid-base pairs of the present invention employs a "ship in a bottle" strategy to achieve high dispersion of transition metal doped atoms in the catalyst. Atom doping alters the surface chemical properties and surface acid-base distribution sites of the oxide catalyst itself, providing new insights into improving the activity of heterogeneous catalysts. Attached Figure Description

[0021] Figure 1 The ultraviolet-visible diffuse reflectance spectra of Embodiment 1, Comparative Example 1, and Comparative Example 2 of the present invention are shown below. Figure 2 The electron spin resonance spectrum of a molybdenum-doped iron oxide catalyst containing a hindered Lewis acid-base pair provided in Example 1 of the present invention; Figure 3 The graphs show the desulfurization performance of the catalysts synthesized in Examples 1, 2, and 3.

[0022] Figure 4 The diagram shows the desulfurization performance of the catalysts synthesized in Example 1 and Comparative Example 1 of this invention. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all instances.

[0024] Example 1

[0025] Weigh 0.0698 g of ammonium molybdate tetrahydrate and 0.1557 g of ferric chloride hexahydrate and dissolve them in a mixed solution of 15 mL of N,N-dimethylformamide and 15 mL of ethylene glycol. Stir well and then add 0.2298 g of 1,3,5-benzenetricarboxylic acid. Stir thoroughly to form a homogeneous mixture.

[0026] The mixture was added to a polytetrafluoroethylene liner and subjected to a solvothermal reaction at 120°C for 12 hours. The resulting sample was gel-like. After centrifugation, washing with anhydrous ethanol, and drying, a precursor of molybdenum-doped iron oxide catalyst was obtained.

[0027] The precursor was then calcined at 700 °C in air at a heating rate of 10 °C / min for 3 hours to obtain a molybdenum-doped iron oxide catalyst containing hindered Lewis acid-base pairs.

[0028] Its hindered Lewis acid-base pair is constructed with an iron atom adjacent to a molybdenum atom as the Lewis acid site and a molybdenum atom adjacent to an oxygen vacancy as the Lewis base site. (Corresponding to the attached...) Figure 1 The absorption peak position in the ultraviolet-visible diffuse reflectance spectrum shows a redshift. Figure 2 The electron spin resonance spectroscopy revealed the presence of oxygen vacancies in the catalyst.

[0029] Catalytic oxidation desulfurization of oil products: 20 mg of catalyst was mixed with 20 mL of solution containing 200 mg kg of catalyst. -1 The mixture was stirred with DBT and oxygen was introduced (120 mL / min). The mixture was then stirred in an oil bath at 600 rpm and reacted at 120°C. Samples were taken at regular intervals, and the sulfur content in the simulated oil was determined using gas chromatography. The results are attached. Figure 3 and attached Figure 4 As shown, the catalyst corresponding to Example 1 can achieve a desulfurization rate of 100% within 3 hours.

[0030] Example 2

[0031] (1) Weigh ammonium tungstate and chromium nitrate at a metal source molar ratio of 2:10, dissolve them in a mixed solution of 15 mL N,N-dimethylformamide and 15 mL ethylene glycol, stir evenly, then add 0.2298 g 1,3,5-benzenetricarboxylic acid and stir thoroughly to form a homogeneous mixture.

[0032] (2) The mixture was added to the polytetrafluoroethylene liner and subjected to a solvothermal reaction at 120°C for 12 hours. The resulting sample was gel-like. After centrifugation, washing with anhydrous ethanol, and drying, a precursor of tungsten-doped chromium oxide catalyst was obtained.

[0033] (3) The precursor was then calcined at 700°C in air at a heating rate of 10°C / min for 3 hours to obtain a tungsten-doped chromium oxide catalyst containing hindered Lewis acid-base pairs.

[0034] Example 3

[0035] (1) Weigh ammonium vanadate and aluminum nitrate according to the metal source molar ratio of 3:10, dissolve them in a mixed solution of 15 mL N,N-dimethylformamide and 15 mL ethylene glycol, stir evenly, then add 0.2298 g 1,3,5-benzenetricarboxylic acid, and stir thoroughly to form a homogeneous mixture.

[0036] (2) The mixture was added to the polytetrafluoroethylene liner and subjected to a solvothermal reaction at 120°C for 12 hours. The resulting sample was gel-like. After centrifugation, washing with anhydrous ethanol, and drying, a precursor of vanadium-doped alumina catalyst was obtained.

[0037] (3) The precursor was then calcined at 700°C in air at a heating rate of 10°C / min for 3 hours to obtain a vanadium-doped alumina catalyst containing hindered Lewis acid-base pairs.

[0038] Comparative Example 1 (1) Weigh 0.0698 g of ammonium molybdate tetrahydrate and 0.1557 g of ferric chloride hexahydrate and dissolve them in a mixed solution of 15 mL of N,N-dimethylformamide and 15 mL of ethylene glycol. Stir until homogeneous to form a uniform mixture.

[0039] (2) The mixture was added to the polytetrafluoroethylene liner and subjected to a solvothermal reaction at 120°C for 12 hours. The resulting sample was gel-like. It was centrifuged, washed with anhydrous ethanol, and dried to obtain the mixture precursor.

[0040] (3) Then the precursor was calcined at 700℃ in air for 3 hours at a heating rate of 10℃ / min to obtain a molybdenum-iron bimetallic oxide catalyst with low Lewis acid-base matching.

[0041] Catalytic oxidation desulfurization of oil products: 20 mg of catalyst was mixed with 20 mL of solution containing 200 mg kg of catalyst. -1 The mixture was stirred with DBT and oxygen was introduced (120 mL / min). The mixture was then stirred in an oil bath at 600 rpm and reacted at 120°C. Samples were taken at regular intervals, and the sulfur content in the simulated oil was determined using gas chromatography. The results are attached. Figure 4 As shown. The catalyst obtained in Comparative Example 1 still had a latent desulfurization activity after 3 hours of reaction, with a desulfurization rate of less than 20%; after 7 hours of reaction, the desulfurization rate reached 88.0%; and after 8 hours of reaction, the desulfurization rate reached 100%.

[0042] The comparative example of desulfurization performance shows that adding 1,3,5-benzenetricarboxylic acid to the precursor is beneficial for forming MOF coating structure. Its abundant pores are more conducive to the dispersion of doped metal sources. During calcination, it is easy to construct Lewis acid-base pairs with suitable acidity and basicity, which is beneficial to desulfurization performance.

[0043] Comparative Example 2 0.1557 g of ferric chloride hexahydrate was dissolved in a mixed solution of 15 mL N,N-dimethylformamide and 15 mL ethylene glycol, and then 0.2298 g of 1,3,5-benzenetricarboxylic acid was added. The mixture was stirred thoroughly to form a homogeneous solution. Further, the solution was subjected to a solvothermal reaction at 120 °C for 12 hours. The resulting sample was centrifuged, washed with anhydrous ethanol, and dried to obtain the precursor MIL-100(Fe). The precursor was calcined at 700 °C in air at a rate of 10 °C / min for 3 hours to obtain the Fe₂O₃ catalyst.

[0044] 20 mg of iron oxide catalyst was mixed with 20 mL of DBT containing 200 mg kg⁻¹, and oxygen was introduced (120 mL / min). The mixture was stirred in an oil bath at 600 rpm and reacted at 120 °C for 4 hours. Samples were taken at regular intervals, and the sulfur content in the simulated oil was determined using gas chromatography. The desulfurization performance is shown in the attached figure. Figure 3 As shown, under these reaction conditions, the removal rate of DBT by the Fe2O3 catalyst was still less than 10% after 4 hours of reaction.

[0045] Comparative Example 3 Ferric molybdate was synthesized by a coprecipitation method. First, ferric nitrate was dissolved in distilled water and set aside. Then, it was added dropwise to a prepared pre-acidified (pH=2, nitric acid) ammonium molybdate solution. The prepared solution was reacted at 80°C for 3 hours, filtered (without washing or drying), and calcined at 700°C for 3 hours to obtain the ferric molybdate catalyst.

[0046] 20 mg of ferric molybdate catalyst was mixed with 20 mL of DBT containing 200 mg kg⁻¹, and oxygen was introduced (120 mL / min). The mixture was stirred in an oil bath at 600 rpm and reacted at 120 °C for 4 hours. Samples were taken at regular intervals, and the sulfur content in the simulated oil was determined using gas chromatography. The desulfurization performance is shown in the attached figure. Figure 3 As shown, under these reaction conditions, the removal rate of DBT by the Fe2O3 catalyst is less than 10% after 4 hours of reaction.

[0047] The various modifications described in these examples will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention.

Claims

1. The use of a polymetallic oxide containing hindered Lewis acid-base pairs for the catalytic oxidation of aromatic sulfur-containing compounds in diesel fuel, wherein the polymetallic oxide containing hindered Lewis acid-base pairs is prepared by the following steps: (1) Dissolve the transition metal dopant source and the coordination metal source in a mixed solution of N,N-dimethylformamide and ethylene glycol. After stirring until there are no obvious particles, add a certain amount of 1,3,5-benzenetricarboxylic acid and stir thoroughly to form a homogeneous mixture. The transition metal doping source is one or more of ammonium molybdate tetrahydrate, ammonium molybdate, ammonium tungstate, ammonium metavanadate, or titanate; the coordination metal source is one of ferric chloride hexahydrate, ferric nitrate nonahydrate, chromium nitrate, or aluminum nitrate nonahydrate. (2) The mixture prepared in step (1) is added to the polytetrafluoroethylene liner and subjected to a solvothermal reaction at a certain temperature. After the reaction is completed, it is cooled to room temperature, centrifuged, washed with anhydrous ethanol, and dried to obtain the catalyst precursor. (3) The precursor sample obtained in step (2) is placed in a tube furnace and heated to the calcination temperature in a gas atmosphere at a certain heating rate to obtain a multi-metal oxide catalyst containing hindered Lewis acid-base pairs.

2. The use as described in claim 1, characterized in that, In step (1), the transition metal doping source is ammonium molybdate tetrahydrate, and the coordination metal source is ferric chloride hexahydrate.

3. The use as described in claim 1, characterized in that, In step (1), the molar ratio of metal ions in the transition metal doped source and the coordination metal source is 0.5:10~3:

10.

4. The use as described in claim 1, characterized in that, In step (1), the volume ratio of N,N-dimethylformamide to ethylene glycol in the mixed solution of N,N-dimethylformamide and ethylene glycol is 1:

1.

5. The use as described in claim 1, characterized in that, In step (1), the molar ratio of 1,3,5-benzenetricarboxylic acid to the coordinating metal source is 1.5~2:

1.

6. The use as described in claim 1, characterized in that, In step (2), the temperature of the solvothermal reaction is 100~140℃ and the time is 6-18 hours.

7. The use as described in claim 1, characterized in that, In step (3), the heating rate is 5~10℃ / min, the calcination temperature is 400~800℃, and the calcination time is 1~6h; the gas atmosphere is: air, oxygen, or a mixed gas containing a certain oxygen component.